Mucocele of the appendix: Incidental finding of a rare occurrence - Malla, Ashish B.; Sah, Rakesh Kumar (Grande Medical Journal, 2019)
Mucocele of the appendix is a rare disease. Clinically, appendeceal mucocele (AM) is an incidental finding or it may mimic appendicitis. In AM, distension of the appendix is caused by mucus, the source of which can be benign or malignant. For the benign disease, appendectomy alone is sufficient but for malignant conditions adjunct treatments are needed. Proper pre-operative evaluation is imperative to distinguish between benign and malignant causes in order to guide the management and reduce complications. For the definitive diagnosis, histology and immunohistochemistry are required. We report an incidental finding of an appendeceal mucocele in a kidney donor during pre-transplant evaluation.